Hybridity of the Jewish Diaspora Characters in Pearl S. Buck's Novel Peony (1948) - Ayu Ratna Ningtyas (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
This research aims to investigate the hybridity of the Jewish diaspora characters in Pearl Sydenstricker Buck's novel Peony (1948). Peony (1948) raises identity issues especially within the Jewish diaspora characters. The qualitative method is used in collecting, interpreting, and analyzing the novel Peony as the main data. The data analysis uses the theory of identity and hybridity in analyzing characters in the novel. The theory of identity is used to analyze the intercultural interactions among the characters of different ethnic backgrounds which shapes a contestation of identity among characters in the novel. Hybridity theory is also used to analyze how Jewish diaspora characters transform into hybrid characters in responding the contestation of identity. Through the observation of how the contestation of identity happens among the characters, this research shows that the Jewish diaspora characters in Peony use hybridity as strategy to win the contestation of identity among characters in the novel.